Correlation between Anthropometric Parameters and Anterior Cruciate Ligament, Hamstring Tendon, and Posterior Horn of Medial and Lateral Meniscus Sizes - Albishi, Waleed; Aljasser, Sarah; Almalki, Mamdouh; Almohideb, Faten; Alwahabi, Faisal (The Journal of Knee Surgery, 2025)
Anterior cruciate ligament (ACL) reconstruction is commonly performed in orthopedic surgery. Hamstring autografts are frequently used as a graft option for the ACL; however, a clear consensus on optimal graft size is lacking. Here, we aimed to determine the mean ACL, hamstring tendon, and posterior horn meniscal sizes in a Saudi population to determine whether correlations exist between anthropometric data and the widths of the ACL, hamstring tendons (specifically the gracilis and semitendinosus tendons), and medial and lateral meniscal posterior horns. Cross-sectional study is the study design. This study examined 705 knee magnetic resonance images to obtain the following data: ACL proximal origin width, mid-fiber width, distal insertion widths and lengths (in millimeters), semitendinosus and gracilis widths (mm), and posterior horn widths of the bilateral menisci (mm). Anthropometric data included age, sex, weight, height, and body mass index. The mean ± standard deviation of proximal, mid-fiber, and distal ACL attachment widths were 8.4 ± 2.4, 9.9 ± 2.4, and 13.5 ± 2.7 mm, respectively. The mean ACL length was 30.8 ± 4.5 mm, while the mean semitendinosus and gracilis widths were 4.5 ± 1 and 3.3 mm, respectively. The mean medial and lateral meniscus posterior horn widths were 14.1 ± 2.7 and 9.3 ± 1.3 mm, respectively. Height and weight were significantly positively correlated with ACL width and length (p < 0.010) semitendinosus and gracilis tendon (p < 0.010) and posterior horn menisci (p < 0.010) widths. The mean ACL width and length, hamstring tendon (gracilis and semitendinosus) width, and posterior horn width of both menisci were positively correlated with an individual's height and weight. The level of evidence is IV.
Keywords: anterior cruciate ligament; hamstring tendons; meniscus; magnetic resonance images; anthropometric parameters